2022
DOI: 10.1164/rccm.202111-2630oc
|View full text |Cite
|
Sign up to set email alerts
|

International Differences in the Frequency of Chronic Obstructive Pulmonary Disease Exacerbations Reported in Three Clinical Trials

Abstract: Rationale: Exacerbations of chronic obstructive pulmonary disease (COPD) are an important endpoint in multinational clinical treatment trials, but the observed event rate is often lower than anticipated and appears to vary between countries.Objectives: We investigated whether systematic differences in national exacerbation rates might explain this observed variation.Methods: We reviewed data from three large multicenter international randomized trials conducted over an 18-year period with different designs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Moreover, a recent study has documented international differences in the frequency of COPD exacerbations even among patients with the same exacerbation history. 38 It is not clear to what extent the presence of multiple other predictors could explain away such variability. In general, it is likely that prediction models of exacerbations need to be recalibrated to their specific settings (e.g., country, type of care [primary, secondary, or tertiary], and socioeconomic status), as has been demonstrated recently for cardiovascular risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study has documented international differences in the frequency of COPD exacerbations even among patients with the same exacerbation history. 38 It is not clear to what extent the presence of multiple other predictors could explain away such variability. In general, it is likely that prediction models of exacerbations need to be recalibrated to their specific settings (e.g., country, type of care [primary, secondary, or tertiary], and socioeconomic status), as has been demonstrated recently for cardiovascular risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…As ever, the devil is in the detail. Another understudied form of noise in study data was reported by Calverley et al who looked at the effect of country of origin on the observed exacerbation rates of participant in three large clinical trials with different entry criteria 39 . Observed rate was almost always lower than the number of events reported before the study, often substantially so, and some countries included patients with substantially lower exacerbation rates than required to adequately test the effectiveness of the intervention studied (Figure 3).…”
Section: Understanding the Evidencementioning
confidence: 99%
“…The figure shows the within trial exacerbation rate ranking, the within trial exacerbation rate and the percentage contribution of patients to this analysis from that trial and country. Reproduced with permission from Calverley et al [39]…”
Section: Understanding the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, FULFIL was conducted primarily in Eastern Europe, whereas KRONOS was conducted primarily in the US, Japan, and China [ 14 , 15 ]. The countries in which studies are conducted are known to affect exacerbation results [ 17 ]. Additionally, prior exacerbations are well-recognized as a strong predictor of future exacerbation risk [ 18 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%